2020
DOI: 10.18632/oncotarget.27687
|View full text |Cite
|
Sign up to set email alerts
|

Carnosic acid increases sorafenib-induced inhibition of ERK1/2 and STAT3 signaling which contributes to reduced cell proliferation and survival of hepatocellular carcinoma cells

Abstract: Hepatocellular carcinoma (HCC) has increasing worldwide incidence but when unresectable lacks curative options. Treatment with a kinase inhibitor Sorafenib (Sf), while initially effective, results in only short increases in patient survival, thus there is a need for improved treatment regimens. Numerous treatment regimens have been explored wherein Sf is combined with other agents, such as non-toxic botanicals like Curcumin or Silibinin. Recently, we have shown that carnosic acid (CA), a component of the food … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…In contrast to our results, the European Medicines Agency (EMEA) reported that NIL did not induce DNA single-strand breaks in the mouse L5178Y cell line evaluated by the comet assay [ 60 ]. Moreover, the exposure to SOR did not significantly increase DNA double strand breaks, as detected by the neutral comet assay in vitro in human colon adenocarcinoma HT-29 cell line treated with 16 uM for 12 h [ 61 ] and in HepG2 cells treated with 1 µM for 24 h, as detected by the alkaline comet assay [ 62 ]. In contrast, SOR induced DNA damage in vitro in Huh7 [ 62 ], A549 and MCF-7 [ 63 ] cells and in the liver of male albino rats treated with 10 mg/kg body weight daily for two weeks [ 64 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to our results, the European Medicines Agency (EMEA) reported that NIL did not induce DNA single-strand breaks in the mouse L5178Y cell line evaluated by the comet assay [ 60 ]. Moreover, the exposure to SOR did not significantly increase DNA double strand breaks, as detected by the neutral comet assay in vitro in human colon adenocarcinoma HT-29 cell line treated with 16 uM for 12 h [ 61 ] and in HepG2 cells treated with 1 µM for 24 h, as detected by the alkaline comet assay [ 62 ]. In contrast, SOR induced DNA damage in vitro in Huh7 [ 62 ], A549 and MCF-7 [ 63 ] cells and in the liver of male albino rats treated with 10 mg/kg body weight daily for two weeks [ 64 ].…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the exposure to SOR did not significantly increase DNA double strand breaks, as detected by the neutral comet assay in vitro in human colon adenocarcinoma HT-29 cell line treated with 16 uM for 12 h [ 61 ] and in HepG2 cells treated with 1 µM for 24 h, as detected by the alkaline comet assay [ 62 ]. In contrast, SOR induced DNA damage in vitro in Huh7 [ 62 ], A549 and MCF-7 [ 63 ] cells and in the liver of male albino rats treated with 10 mg/kg body weight daily for two weeks [ 64 ]. Diab et al [ 64 ] indicated that DNA damage assessed by the comet assay in vivo was most likely of oxidative origin, as simultaneous treatment of male albino rats with SOR and antioxidants significantly reduced DNA damage induced by SOR.…”
Section: Resultsmentioning
confidence: 99%